A model for understanding the formation energies of nanolamellar phases in transition metal carbides and nitrides. (6th May 2016) - Yu, Hang; Guziewski, Matthew; Thompson, Gregory B; Weinberger, Christopher R
Abstract: In this paper we introduce a stacking-fault based model to understand the energetics of formation of the nanolamellar-based metal carbide and nitride structures. The model is able to reproduce the cohesive energies of the stacking fault phases from density functional theory calculations by fitting the energy of different stacking sequences of metal layers. The model demonstrates that the first and second nearest metal-metal neighbor interactions and the nearest metal-carbon/nitrogen interaction are the dominant terms in determining the cohesive energy of these structures. The model further demonstrates that above a metal to non-metal ratio of 75%, there is no energetic favorability for the stacking faults to form a long-range ordered structure. The model's applicability is demonstrated using the Ta-C system as its case study from which we report that the interfacial energy between ζ -Ta4 C3 and TaC or Ta2 C is negligible. Our results suggest that the closed packed planes of these phases should be aligned and that precipitated phases should be thin, which is in agreement with experiments.